Is Equal Opportunity Enough - Loury, Glenn C. (American Economic Review, 2016)
Affirmative action policies have come increasingly under attack in recent years. Both in the courts and in public discourse questions have been raised about the legitimacy of government efforts on behalf of blacks and other racial minorities.' The criticism seems to have two central themes. First, it is argued that those policies which have been tried have not had a noticeable effect on the economic standing of minority group members. (See James Smith and Finis Welch.) They thus constitute yet another example of costly but ineffective government regulation, according to this view. The second theme strikes more deeply at the foundation of these policies. Its adherents argue that even if effective programs could be designed, they ought not be implemented. There have been philosophical and empirical arguments advanced to support this conclusion. Essentially, the philosophical argument states that it is wrong for government to intervene on behalf of certain groups (and thus, necessarily, at the expense of others); this amounts to reverse discrimination-a visiting of the fathers' sins upon the sons.2 The empirical argument concludes that, moral issues aside, such intervention is unwarranted because the consequences of historical discrimination have been (or will soon be) largely eliminated. (See B. Wattenberg and W. Wilson.) In this essay I would like to offer a defense of affirmative action policies against the second of these thematic criticisms. That is, I shall hold in abeyance questions concerning the efficacy of particular programmatic efforts, and concentrate instead on whether government should in principle be taking actions to facilitate economic progress for minority group members. This would seem to be the logical first step in constructing an intellectual basis for affirmative action policies. Of course, philosophers and legal scholars interested in theories of distributive justice have devoted considerable attention to this question in the past ten years. (See R. Dworkin and T. Nagel.) The approach adopted here differs from these earlier efforts in two ways. First, I shall endeavor to meet the empirical argument directly, by pointing to evidence which suggests that significant racial economic disparity persists. Secondly, I will treat the philosophical argument in a manner in keeping with the economist's traditional approach to the question of the desirability of laissez-faire. This approach is based upon the concept of failure. Intervention is favored over laissez-faire when, because of some externality, the outcome is inefficient. Below I argue that an analogous market failure contributes to the maintenance of economic inequality between racial groups in our society. As such, intervention which redresses this inequality is warranted.